Lithium carbonate and application thereof
Patent Information
- Application Number
- CN202280099232.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-18
- Publication Date
- 2025-04-08
Smart Images

Figure BDA0005274544980000211 
Figure BDA0005274544980000212 
Figure BDA0005274544980000221
Abstract
Description
Technical Field
[0001] The materials, methods and techniques disclosed herein relate to lithium carbonate. More specifically, the disclosure relates to the generation and properties of lithium carbonate, which can be used to prevent overcharging in lithium ion secondary batteries. Background Art
[0002] Lithium secondary batteries have the potential to explode or catch fire when subjected to overcharge or overcurrent. Overcharging of lithium-ion batteries may cause irreversible damage to the battery components and may lead to safety issues. Summary of the invention
[0003] In one aspect, a plurality of lithium carbonate (Li2CO3) particles are disclosed. The lithium carbonate particles may have a D between 0.08 μm and 0.43 μm. v (50) The lithium carbonate particles may have a D between 0.015 μm and 0.5 μm. n (50). The lithium carbonate particles may have a 2 / g to 25m 2 / g. In some cases, the lithium carbonate particles may have a BET surface area between 15m 2 / g to 25m 2 In some cases, the BET surface area is between 17.5 m 2 / g to 22.5m 2 The lithium carbonate particles may contain at least 99 wt % of lithium carbonate.
[0004] In another aspect, a method for preparing lithium carbonate is disclosed. The method may include a first process followed by a second process. The first process may include forming a first lithium carbonate dispersion by combining lithium carbonate particles in a first dispersion medium, wherein the lithium carbonate particles have a D between 5 μm and 8 μm. v (50). The first dispersion medium may include at least one of the following: methanol, ethanol, propanol or N-methyl-2-pyrrolidone. The first process may also include forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO2) particles to the first lithium carbonate dispersion. The first plurality of zirconium oxide particles may have an average diameter between 1.00 mm and 1.80 mm. The first process may also include grinding the first grinding suspension at a first predetermined speed for a first predetermined time period. The first predetermined speed may be between 500 rpm and 1500 rpm. The first predetermined time period may be between 30 min and 300 min. The method may further include, before forming the first grinding suspension, stirring the first lithium carbonate dispersion at 30 rpm to 1000 rpm for 10 min to 20 min.
[0005] The second process may include forming a second lithium carbonate dispersion by combining a plurality of lithium carbonate particles produced by the first process in a second dispersion medium. The second dispersion medium may contain at least one of: methanol, ethanol, propanol or N-methyl-2-pyrrolidone. The second process may further include forming a second grinding suspension by adding a second plurality of zirconium oxide (ZrO2) particles to the second lithium carbonate dispersion. The second plurality of zirconium oxide particles may have an average diameter between 0.20mm and 1.20mm. The second process may also include grinding the second grinding suspension for a second predetermined time period at a second predetermined speed. The second predetermined speed may be between 1000rpm and 2000rpm. The second predetermined time period may be between 60min and 600min. The second process may further include stirring the second lithium carbonate dispersion for 10 to 20min at 1000rpm to 2500rpm before forming the second grinding suspension. In some cases, the second predetermined speed may be between 1200rpm and 1800rpm, and the second predetermined time period may be between 150min and 550min.
[0006] After the second process, the BET surface area of the lithium carbonate particles may increase by 5 to 67 times. After the second process, the lithium carbonate particles may have a surface area of 10 m 2 / g to 25m 2 / g of BET surface area.
[0007] On the other hand, a battery is disclosed. The battery may include a negative electrode, a positive electrode, a separator and a non-aqueous electrolyte. The negative electrode may include a negative electrode active material layer. The negative electrode active material layer may include a binder, a conductive material and a negative electrode active material. The negative electrode active material may include a silicon-carbon composite. In some cases, the negative electrode active material layer includes 90 weight percent (wt%) to 99 wt% of the silicon-carbon composite. The positive electrode may include a positive electrode active material layer. The positive electrode active material layer may include a binder, a conductive material, a positive electrode active material and a plurality of lithium carbonate (Li2CO3) particles. The positive electrode active material may include LiNi 0.8 Co 0.1 Mn 0.1 In some cases, the positive electrode active material layer contains 90 wt % to 99 wt % LiNi 0.8 Co 0.1 Mn 0.1 O2. Lithium carbonate particles can have a 2 / g to 25m 2 / g. In some cases, the lithium carbonate particles have a BET surface area between 15m 2 / g to 25m 2 In some cases, the lithium carbonate particles have a BET surface area between 17.5 m 2 / g to 22.5m2 The lithium carbonate particles may contain at least 99% lithium carbonate. The lithium carbonate particles may have a D between 0.08 μm and 0.43 μm. v (50) The lithium carbonate particles may have a D between 0.015 μm and 0.5 μm. n (50) The positive electrode may contain 0.2 wt% to 1.2 wt% of lithium carbonate particles.
[0008] In another aspect, a method for manufacturing a positive electrode for a lithium ion battery is disclosed. The method for manufacturing the positive electrode may include applying a positive electrode slurry to a positive electrode current collector. The positive electrode slurry may include a binder, a conductive material, a positive electrode active material, and a plurality of lithium carbonate (Li2CO3) particles. The positive electrode active material may include LiNi 0.8 Co 0.1 Mn 0.1 In some cases, the positive electrode slurry comprises 90 wt % to 99 wt % LiNi 0.8 Co 0.1 Mn 0.1 O2. Lithium carbonate particles can have a 2 / g to 25m 2 / g. In some cases, the lithium carbonate particles have a BET surface area between 15m 2 / g to 25m 2 In some cases, the lithium carbonate particles have a BET surface area between 17.5 m 2 / g to 22.5m 2 The lithium carbonate particles may have a BET surface area between 0.08 μm and 0.43 μm. v (50) The lithium carbonate particles may have a D between 0.015 μm and 0.5 μm. n (50) The positive electrode slurry may contain 0.2 wt % to 1.2 wt % of lithium carbonate particles.
[0009] On the other hand, a method for manufacturing a battery is disclosed. The method for manufacturing a battery may include a method for manufacturing a positive electrode. The method for manufacturing a battery may further include a method for manufacturing a negative electrode. The method for manufacturing a negative electrode may include applying a negative electrode slurry to a negative electrode current collector. The negative electrode slurry may include a binder, a conductive material, and a negative electrode active material. The negative electrode active material may include a silicon-carbon composite. The negative electrode slurry may include 90wt% to 99wt% of the silicon-carbon composite.
[0010] There is no specific requirement that materials, techniques or methods involving lithium carbonate contain all of the details characterized herein to obtain some benefit according to the present disclosure. Therefore, the specific embodiments characterized herein are intended as exemplary applications of the described technology, and alternatives are possible. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The same grinding method was used for the following Figure 1-16 Data and images presented in .
[0012] Figure 1 A graph showing the change in particle size of lithium carbonate (Li2CO3) upon exemplary grinding is shown.
[0013] Figure 2 A graph showing the lithium carbonate particle size distribution and bulk density (%) of samples AE as a function of time during grinding is shown.
[0014] Figure 3 A graph showing the change in lithium carbonate particle size and distribution number density (%) as a function of time during grinding for samples AE.
[0015] Figure 4 A graph showing the lithium carbonate particle size distribution and bulk density (%) of sample FL as a function of time during grinding is shown.
[0016] Figure 5 A graph showing the lithium carbonate particle size distribution and corresponding number density (%) of sample FL as a function of time during grinding is shown.
[0017] Figure 6 Scanning electron microscope (SEM) images showing the changes in particle size and morphology over time resulting from grinding.
[0018] Figure 7 Shown is a graph showing the change in BET surface area of lithium carbonate particles over time upon grinding.
[0019] Figure 8-10 A graph showing the results of 8.2A-7.5V overcharge testing of Group A, B, C, and E batteries is shown. Group A batteries contained 1 weight percent (wt%) of ground Li2CO3 particles. Group B batteries contained 0.5 wt% of ground Li2CO3 particles. Group C batteries contained 1 wt% of unground Li2CO3 particles.
[0020] Figure 11-13 A graph showing the results of 12A-5.1V overcharge testing of Group A, B, C, and E batteries is shown. Group A batteries contained 1 wt% of ground Li2CO3 particles. Group B batteries contained 0.5 wt% of ground Li2CO3 particles. Group C batteries contained 1% of unground Li2CO3 particles. Group C batteries did not contain any Li2CO3 particles.
[0021] Figure 14-16A graph showing the results of 8.2A-5.1V overcharge testing of Group A, B, C, and E batteries is shown. Group A batteries contained 1 wt% of ground Li2CO3 particles. Group B batteries contained 0.5 wt% of ground Li2CO3 particles. Group C batteries contained 1 wt% of unground Li2CO3 particles. Group C batteries did not contain any Li2CO3 particles. DETAILED DESCRIPTION
[0022] The materials, methods and techniques disclosed and contemplated herein relate to lithium carbonate particles (Li2CO3). Exemplary lithium carbonate particles may be particularly suitable for battery-related applications. During battery charging, lithium carbonate is electrochemically oxidized to produce carbon dioxide gas. The production of carbon dioxide by lithium carbonate increases the pressure inside the battery. Sufficient gas produced by lithium carbonate can interrupt the current to prevent overcharging. Lithium carbonate particles with a higher BET surface area have an enhanced ability to produce gas and therefore have an improved ability to prevent battery overcharging.
[0023] I. Definitions
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art. In the event of a conflict, this document (including definitions) shall prevail. The following describes example methods and materials, although methods and materials similar or equivalent to those described herein can be used for the practice or testing of the present disclosure. The materials, methods and examples disclosed herein are illustrative only and are not intended to be limiting.
[0025] As used herein, the terms "comprise(s)", "include(s)", "having", "has", "can", "contain(s)" and variations thereof are intended to be open transitional phrases, terms or words that do not exclude the possibility of additional acts or structures. The singular forms "a", "an", and "the" include plural references unless the context clearly dictates otherwise. The present disclosure also contemplates other embodiments, "comprising", "consisting of", and "consisting essentially of", i.e., embodiments or elements presented herein, whether or not explicitly stated.
[0026] Definitions of specific functional groups and chemical terms are described in more detail below.For purposes of this disclosure, chemical elements are identified according to the Periodic Table of the Elements, CAS version, Handbook of Chemistry and Physics (75th Edition), inside cover, and specific functional groups are generally defined as described therein.
[0027] For the recitation of numerical ranges herein, each intervening number with the same degree of precision is expressly contemplated. For example, for the range of 6-9, the numbers 7 and 8 are contemplated in addition to 6 and 9, and for the range of 6.0-7.0, the numbers 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9 and 7.0 are expressly contemplated.
[0028] The modifier "about" used in conjunction with a quantity is inclusive of the specified value and has the meaning dictated by the context (e.g., it includes at least the degree of error associated with the measurement of a particular quantity). The modifier "about" should also be considered to disclose a range defined by the absolute values of the two endpoints. For example, the expression "from about 2 to about 4" also discloses a range of "from 2 to 4". The term "about" can refer to plus or minus 10% of the indicated number. For example, "about 10%" can mean a range of 9% to 11%, while "about 1" can mean 0.9-1.1. Other meanings of "about" may be apparent from the context, such as rounding, so that, for example, "about 1" can also mean from 0.5 to 1.4.
[0029] II. Exemplary Lithium Carbonate Particles
[0030] Exemplary lithium carbonate (Li2CO3) particles can have a variety of chemical compositions and physical properties. Various aspects are discussed below.
[0031] Exemplary lithium carbonate (Li2CO3) particles contain at least 98 weight percent (wt%) lithium carbonate. In some cases, the lithium carbonate particles contain at least 99 wt% lithium carbonate or at least 99.9 wt% lithium carbonate.
[0032] In some cases, exemplary lithium carbonate particles may include up to 2 wt% impurities. In various cases, exemplary lithium carbonate particles include no more than 2 wt% impurities; no more than 1.75 wt% impurities; no more than 1.5 wt% impurities; no more than 1.25 wt% impurities; no more than 1.0 wt% impurities; no more than 0.5 wt% impurities; no more than 0.25 wt% impurities; no more than 0.1 wt% impurities; or no more than 0.01 wt% impurities. Exemplary impurities may include LiCl, LiHCO3, LiOH, water, salts or oxides of metals (e.g., Mg, Na, K, Cu, and Fe), or combinations thereof.
[0033] D v (50) is the volume median of the particles, which means that the volume of particles larger or smaller than the volume median each accounts for 50% of the total volume of the particles. Exemplary lithium carbonate particles may have a D between 0.08 μm and 0.43 μm. v(50). In various cases, the lithium particles may have a D between 0.1 μm and 0.4 μm; between 0.1 μm and 0.35 μm; between 0.15 μm and 0.35 μm; between 0.15 μm and 0.4 μm; between 0.2 μm and 0.4 μm; between 0.2 μm and 0.35 μm; or between 0.25 μm and 0.35 μm. v (50). In various cases, the lithium carbonate particles may have a D of no greater than 0.43 μm; no greater than 0.4 μm; no greater than 0.35 μm; no greater than 0.3 μm; no greater than 0.25 μm; no greater than 0.2 μm; no greater than 0.15 μm; no greater than 0.1 μm; or no greater than 0.08 μm. v (50). In various cases, the lithium carbonate particles may have a D of not less than 0.08 μm; not less than 0.1 μm; not less than 0.15 μm; not less than 0.2 μm; not less than 0.25 μm; not less than 0.3 μm; not less than 0.35 μm; not less than 0.4 μm; or not less than 0.43 μm. v (50).
[0034] D n (50) is the median number of particles, which means that the number of particles larger or smaller than the median number each accounts for 50% of the total number of particles. Exemplary lithium carbonate particles may have a D between 0.015 μm and 0.5 μm. n (50). In various cases, the lithium carbonate particles may have a D between 0.015 μm and 0.45 μm; between 0.02 μm and 0.4 μm; between 0.025 μm and 0.35 μm; between 0.03 μm and 0.3 μm; between 0.035 μm and 0.25 μm; between 0.04 μm and 0.2 μm; or between 0.05 μm and 0.1 μm. n (50). In various cases, the lithium carbonate particles may have a D of no greater than 0.5 μm; no greater than 0.45 μm; no greater than 0.4 μm; no greater than 0.3 μm; no greater than 0.25 μm; no greater than 0.2 μm; no greater than 0.1 μm; no greater than 0.075 μm; no greater than 0.05 μm; no greater than 0.04 μm; no greater than 0.03 μm; no greater than 0.02 μm; or no greater than 0.015 μm. n (50). In various cases, the lithium carbonate particles may have a D of not less than 0.015 μm; not less than 0.02 μm; not less than 0.03 μm; not less than 0.04 μm; not less than 0.05 μm; not less than 0.075 μm; not less than 0.1 μm; not less than 0.2 μm; not less than 0.3 μm; not less than 0.4 μm; or not less than 0.5 μm. n (50).
[0035] Exemplary lithium carbonate particles may have a 10 m 2 / g to 40m 2 / g BET surface area (ie, surface area to weight ratio). In various cases, the lithium carbonate particles may have a BET surface area of 10 m 2 / g to 35m 2 / g; between 10m 2 / g to 30m 2 / g; between 15m 2 / g to 30m 2 / g; between 15m 2 / g to 25m 2 / g; or between 17.5m 2 / g to 22.5m 2 In many cases, the lithium carbonate particles may have a BET surface area of no greater than 40 m 2 / g; not more than 35m 2 / g; not more than 30m 2 / g; not more than 25m 2 / g; not more than 22.5m 2 / g; not more than 20m 2 / g; not more than 17.5m 2 / g; not more than 15m 2 / g; or not more than 10m 2 In many cases, the lithium carbonate particles may have a BET surface area of not less than 10 m 2 / g; not less than 15m 2 / g; not less than 17.5m 2 / g; not less than 20m 2 / g; not less than 22.5m 2 / g; not less than 25m 2 / g; not less than 30m 2 / g; not less than 35m 2 / g; or not less than 40m 2 / g of BET surface area.
[0036] III. Exemplary Methods for Preparing Lithium Carbonate Particles
[0037] An exemplary method can be used to prepare lithium carbonate particles. Various aspects are discussed below.
[0038] Generally, an exemplary method for preparing lithium carbonate particles may include a first process followed by a second process.
[0039] A. Exemplary First Process
[0040] An exemplary first process may include forming a first lithium carbonate dispersion by combining "raw" lithium carbonate (Li2CO3) particles in a first dispersion medium, forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO2) particles to the first lithium carbonate dispersion, and grinding the first grinding suspension at a first predetermined speed for a first predetermined time period.
[0041] An exemplary first dispersion medium may include a polar organic solvent. Exemplary polar organic solvents include methanol (MeOH), ethanol (EtOH), isopropyl alcohol (i-PrOH), N-methyl-2-pyrrolidone (NMP), and combinations thereof.
[0042] Exemplary raw lithium carbonate (Li2CO3) particles for incorporation in the first dispersion medium may have a D between 5 μm and 8 μm. v (50). In various cases, the original lithium carbonate particles may have a D between 5.5 μm and 8 μm; between 5.5 μm and 7.5 μm; between 6 μm and 7.5 μm; or between 6 μm and 7 μm. v (50). In various cases, the original lithium carbonate particles may have a D of no greater than 8 μm; no greater than 7.5 μm; no greater than 7 μm; no greater than 6.5 μm; no greater than 6 μm; no greater than 5.5 μm; or no greater than 5 μm. v (50). In various cases, the original lithium carbonate particles may have a D of not less than 5 μm; not less than 5.5 μm; not less than 6 μm; not less than 6.5 μm; not less than 7 μm; not less than 7.5 μm; or not less than 8 μm. v (50).
[0043] In some cases, the exemplary method may include stirring the first lithium carbonate dispersion before forming the first grinding suspension. The first lithium carbonate dispersion may be stirred for 10 min to 20 min before forming the first grinding suspension. In various cases, the first lithium carbonate dispersion may be stirred for 10 min to 19 min; 10 min to 18 min; 11 min to 17 min; 12 min to 16 min; or 13 min to 15 min before forming the first grinding suspension. In various cases, the first lithium carbonate dispersion may be stirred for no more than 20 min; no more than 19 min; no more than 18 min; no more than 17 min; no more than 16 min; no more than 15 min; no more than 14 min; no more than 13 min; no more than 12 min; no more than 11 min; or no more than 10 min before forming the first grinding suspension. In various cases, the first lithium carbonate dispersion may be stirred for not less than 10 minutes; not less than 11 minutes; not less than 12 minutes; not less than 13 minutes; not less than 14 minutes; not less than 15 minutes; not less than 16 minutes; not less than 17 minutes; not less than 18 minutes; not less than 19 minutes; or not less than 20 minutes before forming the first grinding suspension.
[0044] Before forming the first grinding suspension, the first lithium carbonate dispersion can be stirred at a speed of 30 revolutions per minute (rpm) to 1000rpm. In many cases, before forming the first grinding suspension, the first lithium carbonate dispersion can be stirred at a speed of 50rpm to 1000rpm; 100rpm to 950rpm; 150rpm to 950rpm; 200rpm to 800rpm; 250rpm to 750rpm; 300rpm to 700rpm; 350rpm to 650rpm; 400rpm to 600rpm; or 450rpm to 550rpm. In various cases, prior to forming the first grinding suspension, the first lithium carbonate dispersion can be stirred at a speed of no more than 1000 rpm; no more than 950 rpm; no more than 900 rpm; no more than 850 rpm; no more than 800 rpm; no more than 750 rpm; no more than 700 rpm; no more than 650 rpm; no more than 600 rpm; no more than 550 rpm; no more than 500 rpm; no more than 450 rpm; no more than 400 rpm; no more than 350 rpm; no more than 300 rpm; no more than 250 rpm; no more than 200 rpm; no more than 150 rpm; no more than 100 rpm; no more than 50 rpm; or no more than 30 rpm. In many cases, before forming the first grinding suspension, the first lithium carbonate dispersion can be stirred at a speed of not less than 30rpm; not less than 50rpm; not less than 100rpm; not less than 150rpm; not less than 200rpm; not less than 250rpm; not less than 300rpm; not less than 350rpm; not less than 400rpm; not less than 450rpm; not less than 500rpm; not less than 550rpm; not less than 600rpm; not less than 650rpm; not less than 700rpm; not less than 750rpm; not less than 800rpm; not less than 850rpm; not less than 900rpm; not less than 950rpm; or not less than 1000rpm.
[0045] An exemplary method may include forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO 2 ) particles to a first lithium carbonate dispersion.
[0046] In various cases, the first plurality of zirconium oxide (ZrO2) particles added to the first lithium carbonate dispersion can have an average diameter between 1.00 mm and 1.80 mm. In various cases, the first plurality of zirconium oxide particles have an average diameter between 1.05 mm and 1.75 mm; between 1.10 mm and 1.70 mm; between 1.15 mm and 1.65 mm; between 1.20 mm and 1.60 mm; between 1.25 mm and 1.55 mm; between 1.30 mm and 1.50 mm; or between 1.35 and 1.55. In various cases, the first plurality of zirconium oxide particles have an average diameter of no greater than 1.00 mm; no greater than 1.20 mm; no greater than 1.30 mm; no greater than 1.40 mm; no greater than 1.50 mm; no greater than 1.60 mm; no greater than 1.70 mm; or no greater than 1.80 mm. In various cases, the first plurality of zirconia particles have an average diameter of not less than 1.00 mm; not less than 1.10 mm; not less than 1.20 mm; not less than 1.30 mm; not less than 1.40 mm; not less than 1.50 mm; not less than 1.60 mm; or not less than 1.80 mm.
[0047] In various cases, the lithium carbonate particles can be present in the first grinding suspension at a weight percentage (wt%) of 15 wt% to 45 wt%. In various cases, the lithium carbonate particles can be present in the first grinding suspension at a weight percentage of 15 wt% to 40 wt%; 20 wt% to 45 wt%; 15 wt% to 30 wt%; 30 wt% to 45 wt%; 15 wt% to 25 wt%; 25 wt% to 35 wt%; or 35 wt% to 45 wt%. In various cases, the lithium carbonate particles can be present in the first grinding suspension at a weight percentage of no greater than 45 wt%; no greater than 40 wt%; no greater than 35 wt%; no greater than 30 wt%; no greater than 25 wt%; no greater than 20 wt%; or no greater than 16 wt%. In various cases, the lithium carbonate particles are present in the first grinding suspension at a weight percentage of not less than 15 wt %; not less than 20 wt %; not less than 25 wt %; not less than 30 wt %; not less than 35 wt %; not less than 40 wt %; or not less than 44 wt %.
[0048] In various cases, the weight ratio of the first plurality of zirconium oxide particles to the lithium carbonate particles in the first grinding suspension is from 1:1 to 1:6. In various cases, the weight ratio of the first plurality of zirconium oxide particles to the lithium carbonate particles in the first grinding suspension is from 1:1 to 1:5; 1:2 to 1:5; 1:2 to 1:4; or 1:2 to 1:3. In various cases, the weight ratio of the first plurality of zirconium oxide particles to the lithium carbonate particles in the first grinding suspension is no greater than 1:6; no greater than 1:5; no greater than 1:4; no greater than 1:3; no greater than 1:2; or no greater than 1:1. In various cases, the weight ratio of the first plurality of zirconium oxide particles to the lithium carbonate particles in the first grinding suspension is no less than 1:1; no less than 1:2; no less than 1:3; no less than 1:4; no less than 1:5; or no less than 1:6.
[0049] An exemplary method may include milling a first milled suspension at a first predetermined speed for a first predetermined period of time.
[0050] The first predetermined grinding speed for grinding can be between 500 revolutions per minute (rpm) and 1500 rpm. In many cases, the first predetermined grinding speed is between 600 rpm and 1500 rpm; between 600 rpm and 1400 rpm; between 700 rpm and 1400 rpm; between 700 rpm and 1300 rpm; between 800 rpm and 1300 rpm; between 800 rpm and 1200 rpm; between 900 rpm and 1200 rpm; or between 900 rpm and 1100 rpm. In many cases, the first predetermined grinding speed does not exceed 1500 rpm; does not exceed 1400 rpm; does not exceed 1300 rpm; does not exceed 1200 rpm; does not exceed 1100 rpm; does not exceed 1000 rpm; does not exceed 900 rpm; does not exceed 800 rpm; does not exceed 700 rpm; does not exceed 600 rpm; or does not exceed 500 rpm. In various cases, the first predetermined milling speed is not less than 500 rpm; not less than 600 rpm; not less than 700 rpm; not less than 800 rpm; not less than 900 rpm; not less than 1000 rpm; not less than 1100 rpm; not less than 1200 rpm; not less than 1300 rpm; or not less than 1500 rpm.
[0051] The first predetermined grinding time period for grinding can be between 30 minutes and 300 minutes. In many cases, the first predetermined grinding time period is between 40 minutes and 300 minutes; between 50 minutes and 250 minutes; between 60 minutes and 200 minutes; between 70 minutes and 150 minutes; between 80 minutes and 100 minutes. In many cases, the first predetermined grinding time period is no more than 300 minutes; no more than 250 minutes; no more than 200 minutes; no more than 150 minutes; no more than 100 minutes; no more than 90 minutes; no more than 80 minutes; no more than 70 minutes; no more than 60 minutes; no more than 50 minutes; no more than 40 minutes; or no more than 30 minutes. In many cases, the first predetermined grinding time period is not less than 30 minutes; not less than 40 minutes; not less than 50 minutes; not less than 60 minutes; not less than 70 minutes; not less than 80 minutes; not less than 90 minutes; not less than 100 minutes; not less than 150 minutes; not less than 200 minutes; not less than 250 minutes; or not less than 300 minutes.
[0052] Before, during or after grinding, the temperature of the first grinding suspension may be between 15° C. and 50° C. In various cases, the temperature of the first grinding suspension may be between 20° C. and 50° C.; between 20° C. and 45° C.; between 25° C. and 45° C.; between 25° C. and 40° C.; or between 30° C. and 40° C. In various cases, the temperature of the first grinding suspension may not exceed 50° C.; not exceed 45° C.; not exceed 40° C.; not exceed 35° C.; not exceed 30° C.; not exceed 25° C.; not exceed 20° C.; or not exceed 15° C.
[0053] For an exemplary first process, the ambient temperature during the grinding process may be from 25°C to 45°C. In various cases, for the first process, the ambient temperature during the grinding process may be from 25°C to 40°C; from 25°C to 35°C; or from 30°C to 35°C. In various cases, for the first process, the ambient temperature during the grinding process may be no more than 40°C; no more than 35°C; no more than 30°C; or no more than 25°C. In various cases, the ambient temperature during the grinding process is no less than 25°C; no less than 30°C; no less than 35°C; or no less than 40°C.
[0054] For an exemplary first process, the ambient humidity during the grinding process may be less than 10%. In various cases, for the first process, the ambient humidity during the grinding process may be less than 9%; less than 8%; less than 7%; less than 6%; or less than 5%. In various cases, for the first process, the ambient humidity during the grinding process may be no greater than 10%; no greater than 9%; no greater than 8%; no greater than 7%; no greater than 6%; or no greater than 5%.
[0055] B. Exemplary Second Process
[0056] An exemplary second process can include forming a second lithium carbonate dispersion by combining a plurality of lithium carbonate particles produced by the first process in a second dispersion medium, forming a second grinding suspension by adding a second plurality of zirconium oxide (ZrO2) particles to the second lithium carbonate dispersion, and grinding the second grinding suspension at a second predetermined speed for a second predetermined time period.
[0057] An exemplary second dispersion medium may include a polar organic solvent. Exemplary polar organic solvents include methanol (MeOH), ethanol (EtOH), isopropyl alcohol (i-PrOH), N-methyl-2-pyrrolidone (NMP), and combinations thereof.
[0058] In some cases, exemplary methods may include stirring the second lithium carbonate dispersion before forming the second grinding suspension. The second lithium carbonate dispersion may be stirred for 10 min to 20 min before forming the second grinding suspension. In various cases, the second lithium carbonate dispersion may be stirred for 10 min to 19 min; 10 min to 18 min; 11 min to 17 min; 12 min to 16 min; or 13 min to 15 min before forming the second grinding suspension. In various cases, the second lithium carbonate dispersion may be stirred for no more than 20 min; no more than 19 min; no more than 18 min; no more than 17 min; no more than 16 min; no more than 15 min; no more than 14 min; no more than 13 min; no more than 12 min; no more than 11 min; or no more than 10 min before forming the second grinding suspension. In various cases, the second lithium carbonate dispersion may be stirred for not less than 10 minutes; not less than 11 minutes; not less than 12 minutes; not less than 13 minutes; not less than 14 minutes; not less than 15 minutes; not less than 16 minutes; not less than 17 minutes; not less than 18 minutes; not less than 19 minutes; or not less than 20 minutes prior to forming the second grinding suspension.
[0059] Before forming the second grinding suspension, the second lithium carbonate dispersion can be stirred at a speed of 1000 revolutions per minute (rpm) to 2500rpm. In many cases, before forming the second grinding suspension, the second lithium carbonate dispersion can be stirred at a speed of 1100rpm to 2500rpm; 1200rpm to 2400rpm; 1300rpm to 2300rpm; 1400rpm to 2200rpm; 1500rpm to 2100rpm; 1600rpm to 2000rpm; or 1700rpm to 1900rpm. In various cases, prior to forming the second grinding suspension, the second lithium carbonate dispersion can be stirred at a speed of no more than 2500 rpm; no more than 2400 rpm; no more than 2300 rpm; no more than 2200 rpm; no more than 2100 rpm; no more than 2000 rpm; no more than 1900 rpm; no more than 1800 rpm; no more than 1700 rpm; no more than 1600 rpm; no more than 1500 rpm; no more than 1400 rpm; no more than 1300 rpm; no more than 1200 rpm; no more than 1100 rpm; or no more than 1000 rpm. In many cases, prior to forming the second grinding suspension, the second lithium carbonate dispersion can be stirred at a speed of not less than 1000 rpm; not less than 1100 rpm; not less than 1200 rpm; not less than 1300 rpm; not less than 1400 rpm; not less than 1500 rpm; not less than 1600 rpm; not less than 1700 rpm; not less than 1800 rpm; not less than 1900 rpm; not less than 2000 rpm; not less than 2100 rpm; not less than 2200 rpm; not less than 2300 rpm; not less than 2400 rpm; or not less than 2500 rpm.
[0060] An exemplary method may include forming a second milling suspension by adding a second plurality of zirconium oxide (ZrO 2 ) particles to a second lithium carbonate dispersion.
[0061] In various cases, the second plurality of zirconium oxide (ZrO2) particles added to the second lithium carbonate dispersion can have an average diameter between 0.20 mm and 1.20 mm. In various cases, the second plurality of zirconium oxide particles have an average diameter between 0.25 mm and 1.15 mm; between 0.30 mm and 1.10 mm; between 0.35 mm and 1.05 mm; between 0.40 mm and 1.00 mm; between 0.45 mm and 0.95 mm; between 0.50 mm and 0.90 mm; between 0.55 and 0.85; or between 0.60 and 0.80. In various cases, the second plurality of zirconium oxide particles can have an average diameter of no greater than 1.20 mm; no greater than 1.10 mm; no greater than 1.00 mm; no greater than 0.90 mm; no greater than 0.80 mm; no greater than 0.70 mm; no greater than 0.60 mm; no greater than 0.50 mm; no greater than 0.40 mm; no greater than 0.30 mm; or no greater than 0.20 mm. In various cases, the second plurality of zirconium oxide particles can have an average diameter of no less than 0.20 mm; no less than 0.30 mm; no less than 0.40 mm; no less than 0.50 mm; no less than 0.60 mm; no less than 0.70 mm; no less than 0.80 mm; no less than 0.90 mm; no less than 1.00 mm; no less than 1.10 mm; or no less than 1.20 mm.
[0062] In various cases, the lithium carbonate particles can be present in the second grinding suspension at a weight percentage (wt%) of 15 wt% to 45 wt%. In various cases, the lithium carbonate particles can be present in the second grinding suspension at a weight percentage of 15 wt% to 40 wt%; 20 wt% to 45 wt%; 15 wt% to 30 wt%; 30 wt% to 45 wt%; 15 wt% to 25 wt%; 25 wt% to 35 wt%; or 35 wt% to 45 wt%. In various cases, the lithium carbonate particles can be present in the second grinding suspension at a weight percentage of no greater than 45 wt%; no greater than 40 wt%; no greater than 35 wt%; no greater than 30 wt%; no greater than 25 wt%; no greater than 20 wt%; or no greater than 16 wt%. In various cases, the lithium carbonate particles are present in the second grinding suspension at a weight percentage of not less than 15 wt %; not less than 20 wt %; not less than 25 wt %; not less than 30 wt %; not less than 35 wt %; not less than 40 wt %; or not less than 44 wt %.
[0063] In various cases, the weight ratio of the second plurality of zirconium oxide particles to the lithium carbonate particles in the second grinding suspension is from 1:1 to 1:6. In various cases, the weight ratio of the second plurality of zirconium oxide particles to the lithium carbonate particles in the second grinding suspension is from 1:1 to 1:5; 1:2 to 1:5; 1:2 to 1:4; or 1:2 to 1:3. In various cases, the weight ratio of the second plurality of zirconium oxide particles to the lithium carbonate particles in the second grinding suspension is no greater than 1:6; no greater than 1:5; no greater than 1:4; no greater than 1:3; no greater than 1:2; or no greater than 1:1. In various cases, the weight ratio of the second plurality of zirconium oxide particles to the lithium carbonate particles in the second grinding suspension is no less than 1:1; no less than 1:2; no less than 1:3; no less than 1:4; no less than 1:5; or no less than 1:6.
[0064] The second predetermined grinding speed may be between 1000 rpm and 2000 rpm. In many cases, the second predetermined grinding speed is between 1000 rpm and 1900 rpm; between 1100 rpm and 1900 rpm; between 1100 rpm and 1800 rpm; between 1200 rpm and 1800 rpm; between 1200 rpm and 1700 rpm; between 1300 rpm and 1700 rpm; between 1300 rpm and 1600 rpm; between 1400 rpm and 1600 rpm; between 850 rpm and 1200 rpm; or between 900 rpm and 1100 rpm. In various cases, the second predetermined milling speed is no more than 2000 rpm; no more than 1900 rpm; no more than 1800 rpm; no more than 1700 rpm; no more than 1600 rpm; no more than 1500 rpm; no more than 1400 rpm; no more than 1300 rpm; no more than 1200 rpm; no more than 1100 rpm; or no more than 1000 rpm. In various cases, the second predetermined milling speed is not less than 1000 rpm; not less than 1100 rpm; not less than 1200 rpm; not less than 1300 rpm; not less than 1400 rpm; not less than 1500 rpm; not less than 1600 rpm; not less than 1700 rpm; not less than 1800 rpm; not less than 1900 rpm; or not less than 2000 rpm.
[0065] The second predetermined grinding time period for grinding may be between 60 min and 600 min. In various cases, the second predetermined grinding time period may be between 75 min and 600 min; between 100 min and 600 min; between 150 min and 550 min; between 200 min and 500 min; between 250 min and 450 min; between 300 min and 400 min; or between 350 min and 400 min. In various cases, the second predetermined grinding time period may be no more than 600 min; no more than 550 min; no more than 500 min; no more than 450 min; no more than 400 min; no more than 350 min; no more than 300 min; no more than 250 min; no more than 200 min; no more than 150 min; no more than 100 min; no more than 75 min; or no more than 60 min. In many cases, the second predetermined grinding time period may be no less than 60 min; no less than 75 min; no less than 100 min; no less than 150 min; no less than 200 min; no less than 250 min; no less than 300 min; no less than 350 min; no less than 400 min; no less than 450 min; no less than 500 min; no less than 550 min; or no less than 600 min.
[0066] Before, during or after grinding, the temperature of the second grinding suspension may be between 20°C and 40°C. In various cases, the temperature of the second grinding suspension may be between 25°C and 40°C; between 25°C and 35°C; or between 30°C and 35°C. In various cases, the temperature of the second grinding suspension may not exceed 40°C; not exceed 35°C; not exceed 30°C; not exceed 25°C; or not exceed 20°C. In various cases, the temperature of the second grinding suspension may not be less than 20°C; not less than 25°C; not less than 30°C; not less than 35°C; or not less than 40°C.
[0067] For an exemplary second process, the ambient temperature during the grinding process is from 25°C to 45°C. In various cases, for the second process, the ambient temperature during the grinding process is from 25°C to 40°C; from 25°C to 35°C; or from 30°C to 35°C. In various cases, for the second process, the ambient temperature during the grinding process is no more than 40°C; no more than 35°C; no more than 30°C; or no more than 25°C. In various cases, the ambient temperature during the grinding process is no less than 25°C; no less than 30°C; no less than 35°C; or no less than 40°C.
[0068] For the exemplary second process, the ambient humidity during the grinding process can be less than 10%. In various cases, for the second process, the ambient humidity during the grinding process can be less than 9%; less than 8%; less than 7%; less than 6%; or less than 5%. In various cases, for the second process, the ambient humidity during the grinding process can be no greater than 10%; no greater than 9%; no greater than 8%; no greater than 7%; no greater than 6%; or no greater than 5%.
[0069] After the second process, the lithium particles can be dried at a suitable drying temperature for a suitable drying period of time. Typically, the drying operation is performed when a wet milling technique is used.
[0070] In various cases, after the second process, the drying temperature of the lithium carbonate particles may be from 85°C to 140°C. In various cases, the drying temperature may be from 85°C to 135°C; from 90°C to 130°C; from 95°C to 125°C; from 100°C to 120°C; or from 105°C to 115°C. In various cases, the drying temperature may be no more than 140°C; no more than 135°C; no more than 130°C; no more than 125°C; no more than 120°C; no more than 115°C; no more than 110°C; no more than 105°C; no more than 100°C; no more than 95°C; no more than 90°C; or no more than 85°C. In various cases, the drying temperature may be not less than 85°C; not less than 90°C; not less than 95°C; not less than 100°C; not less than 105°C; not less than 110°C; not less than 115°C; not less than 120°C; not less than 125°C; not less than 130°C; not less than 135°C; or not less than 140°C.
[0071] In many cases, after the second process, the drying time period of the lithium carbonate particles may be from 12 hours (h) to 24h. In many cases, the drying time may be from 12h to 23h; from 14h to 22h; from 15h to 21h; from 16h to 20h; or from 17h to 19h. In many cases, the drying time may be no more than 24h; no more than 23h; no more than 22h; no more than 21h; no more than 20h; no more than 19h; no more than 18h; no more than 17h; no more than 16h; no more than 15h; no more than 14h; no more than 13h; or no more than 12h. In many cases, the drying time may be not less than 12h; not less than 13h; not less than 14h; not less than 15h; not less than 16h; not less than 17h; not less than 18h; not less than 19h; not less than 20h; not less than 21h; not less than 22h; not less than 23h; or not less than 24h.
[0072] When comparing the BET surface area of the lithium carbonate particles before and after the exemplary operation, the exemplary method can increase the BET surface area of the lithium carbonate particles by 5 to 62 times. In various cases, the BET surface area of the lithium carbonate particles can be increased by 5 to 62 times; 5 to 30 times; 30 to 60 times; 10 to 60 times; 40 to 60 times; or 45 to 62 times. In various cases, the BET surface area of the lithium carbonate particles can be increased by no more than 60 times; no more than 55 times; no more than 50 times; no more than 45 times; no more than 40 times; no more than 35 times; no more than 30 times; no more than 25 times; no more than 20 times; no more than 15 times; or no more than 10 times. In various cases, the BET surface area of the lithium carbonate particles can be increased by not less than 5 times; not less than 10 times; not less than 15 times; not less than 20 times; not less than 25 times; not less than 30 times; not less than 35 times; not less than 40 times; not less than 45 times; not less than 50 times; not less than 55 times; or not less than 60 times.
[0073] For the exemplary method, after the second process, the lithium particles may have a D between 0.08 μm and 0.43 μm. v (50) and D between 0.015 μm and 0.5 μm n (50).
[0074] IV. Exemplary Applications of Lithium Carbonate Particles
[0075] Exemplary applications of lithium carbonate (Li2CO3) particles may include batteries, such as lithium ion secondary batteries. An exemplary lithium ion battery includes a negative electrode, a positive electrode, and a non-aqueous electrolyte.
[0076] In various cases, the lithium carbonate particles may be present in the slurry at a weight percentage (wt%) of 0.20 wt% to 1.20 wt%. As used herein, "slurry" includes a negative or positive electrode active material, one or more binder materials, one or more carbon materials, one or more solvent media, and lithium carbonate. In various cases, the lithium carbonate particles may be present in the slurry at a weight percentage of 0.20 wt% to 1.10 wt%; 0.30 wt% to 1.00 wt%; 0.40 wt% to 0.90 wt%; 0.50 wt% to 0.80 wt%; or 0.60 wt% to 0.70 wt%. In various cases, the lithium carbonate particles may be present in the slurry at a weight percentage of no more than 1.20 wt %; no more than 1.10 wt %; no more than 1.00 wt %; no more than 0.90 wt %; no more than 0.80 wt %; no more than 0.70 wt %; no more than 0.60 wt %; no more than 0.50 wt %; no more than 0.40 wt %; no more than 0.30 wt %; or no more than 0.20 wt %. In various cases, the lithium carbonate particles may be present in the slurry at a weight percentage of no less than 0.20 wt %; no less than 0.30 wt %; no less than 0.40 wt %; no less than 0.50 wt %; no less than 0.60 wt %; no less than 0.70 wt %; no less than 0.80 wt %; no less than 0.90 wt %; no less than 1.00 wt %; no less than 1.10 wt %; or no less than 1.20 wt %.
[0077] A. Negative electrode
[0078] The exemplary negative electrode may generally include a negative electrode active material layer and a negative electrode current collector. The exemplary negative electrode active material layer may include a negative electrode active material, a binder, and a conductive material. The exemplary negative electrode active material is not particularly limited and may include carbon, such as natural or artificial graphite. In many cases, the negative electrode active material may be a carbon composite, such as a silicon graphite composite ("Si / graphite").
[0079] An exemplary negative electrode active material layer may contain 90 wt% to 99 wt% of the negative electrode active material. In various cases, the exemplary negative electrode may contain 91 wt% to 99 wt% of the negative electrode active material; 92 wt% to 98 wt% of the negative electrode active material; 93 wt% to 97 wt% of the negative electrode active material; or 94 wt% to 96 wt% of the negative electrode active material. In various cases, the exemplary negative electrode active material layer may contain no more than 99 wt% of the negative electrode active material; no more than 98 wt% of the negative electrode active material; no more than 97 wt% of the negative electrode active material; no more than 96 wt% of the negative electrode active material; no more than 95 wt% of the negative electrode active material; no more than 94 wt% of the negative electrode active material; no more than 93 wt% of the negative electrode active material; no more than 92 wt% of the negative electrode active material; no more than 91 wt% of the negative electrode active material; or no more than 90 wt% of the negative electrode active material. In various cases, an exemplary negative electrode active material layer may contain not less than 90 wt % of a negative electrode active material; not less than 91 wt % of a negative electrode active material; not less than 92 wt % of a negative electrode active material; not less than 93 wt % of a negative electrode active material; not less than 94 wt % of a negative electrode active material; not less than 95 wt % of a negative electrode active material; not less than 96 wt % of a negative electrode active material; not less than 97 wt % of a negative electrode active material; not less than 98 wt % of a negative electrode active material; or not less than 99 wt % of a negative electrode active material.
[0080] The exemplary negative electrode can be manufactured by coating a negative electrode slurry including negative electrode active material layer components (which may include negative electrode active material, binder and conductive material) onto a current collector and drying the slurry on the current collector. The negative electrode active material layer can be further compacted onto the current collector using a pressing method known to those of ordinary skill in the art.
[0081] B. Positive electrode
[0082] An exemplary positive electrode may generally include a positive electrode active material layer and a positive electrode current collector. An exemplary positive electrode active material layer may include a positive electrode active material, a binder, a conductive material, and lithium carbonate (Li2CO3) particles described herein. An exemplary positive electrode active material is not particularly limited and may include a lithium metal oxide (e.g., LiNi 0.8 Co 0.1 Mn 0.1 O2).
[0083] An exemplary positive electrode may include 90 wt% to 99 wt% of the positive electrode active material. In various cases, the exemplary positive electrode may include 91 wt% to 99 wt% of the positive electrode active material; 92 wt% to 98 wt% of the positive electrode active material; 93 wt% to 97 wt% of the positive electrode active material; or 94 wt% to 96 wt% of the positive electrode active material. In various cases, the exemplary positive electrode may include no more than 99 wt% of the positive electrode active material; no more than 98 wt% of the positive electrode active material; no more than 97 wt% of the positive electrode active material; no more than 96 wt% of the positive electrode active material; no more than 95 wt% of the positive electrode active material; no more than 94 wt% of the positive electrode active material; no more than 93 wt% of the positive electrode active material; no more than 92 wt% of the positive electrode active material; no more than 91 wt% of the positive electrode active material; or no more than 90 wt% of the positive electrode active material. In various cases, an exemplary positive electrode may contain not less than 90 wt % of the positive electrode active material; not less than 91 wt % of the positive electrode active material; not less than 92 wt % of the positive electrode active material; not less than 93 wt % of the positive electrode active material; not less than 94 wt % of the positive electrode active material; not less than 95 wt % of the positive electrode active material; not less than 96 wt % of the positive electrode active material; not less than 97 wt % of the positive electrode active material; not less than 98 wt % of the positive electrode active material; or not less than 99 wt % of the positive electrode active material.
[0084] An exemplary positive electrode may include 0.20 wt % to 1.20 wt % lithium carbonate (Li2CO3) particles, which are prepared using the methods described herein. In various cases, the weight percentage of lithium carbonate (Li2CO3) particles present in the positive electrode may be 0.20 wt % to 1.10 wt %; 0.30 wt % to 1.00 wt %; 0.40 wt % to 0.90 wt %; 0.50 wt % to 0.80 wt %; or 0.60 wt % to 0.70 wt %. In various cases, the weight percentage of lithium carbonate (Li2CO3) particles present in the positive electrode can be no more than 1.20wt%; no more than 1.10wt%; no more than 1.00wt%; no more than 0.90wt%; no more than 0.80wt%; no more than 0.70wt%; no more than 0.60wt%; no more than 0.50wt%; no more than 0.40wt%; no more than 0.30wt%; or no more than 0.20wt%. In various cases, the weight percentage of lithium carbonate (Li2CO3) particles present in the positive electrode can be no less than 0.20wt%; no less than 0.30wt%; no less than 0.40wt%; no less than 0.50wt%; no less than 0.60wt%; no less than 0.70wt%; no less than 0.80wt%; no less than 0.90wt%; no less than 1.00wt%; no less than 1.10wt%; or no less than 1.20wt%.
[0085] The exemplary positive electrode can be manufactured by coating a positive electrode slurry including positive electrode active material layer components (which may include positive electrode active material, binder, conductive material and lithium carbonate (Li2CO3) particles) onto a positive electrode current collector and drying the slurry on the current collector. The positive electrode active material layer can be further compacted onto the current collector using a pressing method known to those of ordinary skill in the art. The exemplary positive electrode slurry can be manufactured by combining the positive electrode active material layer components (positive electrode active material, binder and conductive material) and adding a suitable solvent (e.g., N-methylpyrrolidone).
[0086] C. Electrolytes
[0087] The nonaqueous electrolyte for lithium ion batteries including the lithium carbonate (Li2CO3) particles described herein is not particularly limited. Typically, the exemplary nonaqueous electrolyte includes at least one lithium (Li) salt and a nonaqueous solvent.
[0088] An exemplary lithium ion secondary battery may be manufactured by using methods known to those of ordinary skill in the art.
[0089] V. Experimental Examples
[0090] Without limiting the scope of the present disclosure, various experimental examples of the embodiments discussed above were prepared and the results are discussed below.
[0091] Example 1: Changes in Li2CO3 particle size during grinding
[0092] Particle size measurements of lithium carbonate (Li2CO3) samples (samples AF and FL) were performed using laser particle size analysis. For the following grinding tests, 0.2 g of each lithium carbonate sample was dispersed in 10 mL of ethanol. Each sample was analyzed by a Malvern laser particle size analyzer, background removed, then added to 600 mL and processed until 8-15% shadowing was observed.
[0093] Lithium carbonate (Li2CO3) samples (samples AF and FL) were ground for different time periods and the resulting lithium carbonate particle size D was measured. v (50)(μm) and D N (50) (μm). For pre-grinding, 0.9 kg of crude lithium carbonate (Li2CO3) was added to 4 kg of ethanol (EtOH) in a 20-liter mixer and mixed at a speed of 30-2500 rpm for 15 min to prepare the samples. The grinding mixing speed for all samples was 1000 rpm.
[0094] Table 1. Lithium carbonate particle size (D v (50) and D N (50)).
[0095]
[0096] Table 2. Lithium carbonate particle size (D v (50) and D N (50)).
[0097]
[0098] Example 2: BET surface area
[0099] The BET surface area measurement method used to determine the following BET surface areas is based on GB / T19587-2004. 2 / g initial BET surface area and 0.3wt% impurities of crude lithium carbonate (Li2CO3) particles were ground for time periods of 10min, 30min, 90min, 150min, 210min, 270min and 390min (samples D, F, H, I, J, K and L, respectively). The BET surface area was measured for each ground lithium carbonate sample. The BET surface area was determined using a Tristar 2030 instrument, and the test standard was GB / T 19587-2017 "Determination of solid specific surface area by gas adsorption BET method". Generally, the test method includes using 0.3g-1g sample, heating the sample to 200°C and degassing for 2 hours, and measuring the surface area with a standard nitrogen system after degassing.
[0100] The BET surface area results are shown in Tables 3 and Figure 7 As shown in Table 3 below, after grinding lithium carbonate for 390 min, the BET surface area of sample L is 20.74 m 2 Without wishing to be bound by a particular theory, the inventors hypothesize that grinding for longer periods of time (>390 min) can yield values up to 40 m 2 / g of BET surface area.
[0101] Table 3. BET surface area of lithium carbonate particles of samples A0-L.
[0102]
[0103] Example 3: Overcharge Test
[0104] For the following overcharge experiments, groups A, B, C, and E lithium ion batteries were tested. Group A batteries were prepared with 1 wt% lithium carbonate. Group B batteries were prepared with 0.5 wt% lithium carbonate. The lithium carbonate used in Group A batteries and Group B batteries was Sample L lithium carbonate, as shown in Table 3 above, where the lithium carbonate was prepared by grinding for 390 min.
[0105] The C group of cells were prepared with 1 wt% lithium carbonate, where the lithium carbonate was not prepared by grinding (Sample A0, Table 3 above). 0.8 Co 0.1 Mn 0.1 O2 was used as the positive electrode active material, silicon graphite composite was used as the negative electrode active material, and LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) / fluoroethylene carbonate (FEC) was used as the electrolyte. Tables 4-6 show the results of three overcharge experiments (8.2A-7.5V (100% SOC), 12.0A-5.1V (100% SOC), and 8.0A-5.1V (0% SOC)).
[0106] Table 4.8.2A - 7.5V (100% SOC) Overcharge Test (CID = Current Interrupt Device, SOC = State of Charge)
[0107]
[0108]
[0109] Table 5.1 2.0A-5.1V (100% SOC) Overcharge Test (CID = Current Interrupt Device, SOC = State of Charge)
[0110]
[0111]
[0112] Table 6.8.0A-5.1V (0% SOC) Overcharge Test (CID = Current Interrupt Device, SOC = State of Charge)
[0113]
[0114] As shown above, Group A and Group B passed all three overcharge tests, while Group C and Group E failed all three overcharge tests. From the comparison data of Group A and Group B with Group C and Group D, it can be seen that the addition of a large surface area (21.1m 2 / g) of ground Li2CO3 particles, which accelerates the gas generation rate during overcharging, thereby reducing the corresponding current interrupt device (CID) opening time and CID opening temperature.
[0115] Comparing the three types of overcharge tests (8.2A-7.5V (100% SOC), 12.0A-5.1V (100% SOC) and 8.0A-5.1V (0% SOC)), the 8.2A-5.1V overcharge test starts from 0% state of charge (SOC), which generates more heat, resulting in a higher maximum battery temperature than the 8.2A-7.5V and 12.0A-5.1V overcharge tests, which start from 100% state of charge (SOC). Comparing the 8.2A-7.5V overcharge test data with the 12.0A-5.1V overcharge test data, it is shown that the increase in charging current reduces the CID open time.
[0116] The foregoing description of specific aspects will reveal the general nature of the technology so fully that others can easily modify and / or adapt the various applications of these specific aspects without departing from the general concept of the present disclosure by applying knowledge within the skills of the art without undue experimentation. Therefore, based on the teachings and guidance presented herein, such adaptations and modifications are intended to fall within the meaning and range of equivalents of the disclosed aspects. It should be understood that the terms or terminology herein are for the purpose of description rather than limitation, so that the terms or terminology of this specification will be interpreted by those skilled in the art based on the teachings and guidance.
[0117] The breadth and scope of the present disclosure should not be limited by any of the above-described exemplary aspects, but should be defined only in accordance with the following claims and their equivalents.
[0118] All publications, patents, patent applications and / or other documents cited in this application are incorporated by reference in their entirety for all purposes to the same extent as if each individual publication, patent, patent application and / or other document was individually indicated to be incorporated by reference for all purposes.
[0119] For reasons of completeness, various aspects of the present technology are set forth in the following numbered embodiments:
[0120] Embodiment 1. A plurality of lithium carbonate (Li2CO3) particles comprising:
[0121] at least 98 weight percent (wt%) lithium carbonate, the particles having:
[0122] D between 0.08 μm and 0.43 μm v (50);
[0123] D between 0.015 μm and 0.5 μm n (50); and
[0124] In 10m 2 / g to 25m 2 / g of BET surface area.
[0125] Embodiment 2. The lithium carbonate (Li2CO3) particles according to Embodiment 1, wherein the D v (50) Between 0.15 μm and 0.35 μm.
[0126] Embodiment 3. The lithium carbonate (Li2CO3) particles according to Embodiment 1 or 2, wherein the D n (50) Between 0.03 μm and 0.3 μm.
[0127] Embodiment 4. The lithium carbonate (Li2CO3) particles according to any one of Embodiments 1-3, wherein the BET surface area is 15 m 2 / g to 25m 2 / g.
[0128] Embodiment 5. The lithium carbonate (Li2CO3) particles according to any one of Embodiments 1-4, wherein the BET surface area is 17.5 m 2 / g to 22.5m 2 / g.
[0129] Embodiment 6. The lithium carbonate (Li2CO3) particles according to any one of Embodiments 1-5, wherein the lithium carbonate particles comprise at least 99 wt% lithium carbonate.
[0130] Embodiment 7. A method for preparing lithium carbonate, comprising:
[0131] A first process is followed by a second process, wherein the first process comprises:
[0132] The first lithium carbonate dispersion is formed by combining lithium carbonate particles in a first dispersion medium, wherein the lithium carbonate particles have a D between 5 μm and 8 μm. v (50);
[0133] forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO2) particles to a first lithium carbonate dispersion; and
[0134] grinding the first grinding suspension at a first predetermined speed for a first predetermined time period, the first predetermined speed being between 500 rpm and 1500 rpm, and the first predetermined time period being between 30 min and 300 min; and
[0135] The second process includes:
[0136] forming a second lithium carbonate dispersion by combining a plurality of lithium carbonate particles produced by the first process in a second dispersion medium;
[0137] forming a second grinding suspension by adding a second plurality of zirconium oxide (ZrO2) particles to a second lithium carbonate dispersion; and
[0138] The second grinding suspension is ground at a second predetermined speed for a second predetermined period of time, the second predetermined speed being between 1000 rpm and 2000 rpm, and the second predetermined period of time being between 60 min and 600 min.
[0139] Embodiment 8. The method according to embodiment 7, wherein the first predetermined speed is between 600 rpm and 1400 rpm, and the first predetermined time period is between 50 min and 250 min.
[0140] Embodiment 9. The method according to embodiment 7 or 8, wherein the second predetermined speed is between 1200 rpm and 1800 rpm, and the second predetermined time period is between 150 min and 550 min.
[0141] Embodiment 10. The method according to any one of embodiments 7-9, wherein the first dispersion medium comprises at least one of the following: methanol, ethanol, propanol, or N-methyl-2-pyrrolidone.
[0142] Embodiment 11. The method according to any one of embodiments 7-10, wherein the second dispersion medium comprises at least one of the following: methanol, ethanol, propanol, or N-methyl-2-pyrrolidone.
[0143] Embodiment 12. The method of any one of Embodiments 7-11, wherein the first plurality of zirconium oxide particles have an average diameter between 1.00 mm and 1.80 mm.
[0144] Embodiment 13. The method of any one of Embodiments 7-12, wherein the second plurality of zirconium oxide particles have an average diameter between 0.20 mm and 1.20 mm.
[0145] Embodiment 14. The method according to any one of embodiments 7-13, wherein after the second process, the lithium carbonate (Li2CO3) particles have a D between 0.08 μm and 0.43 μm. v (50) and D between 0.015 μm and 0.5 μm n (50).
[0146] Embodiment 15. The method according to any one of Embodiments 7-14, further comprising stirring the first lithium carbonate dispersion at 30 rpm to 1000 rpm for 10 min to 20 min before forming the first grinding suspension.
[0147] Embodiment 16. The method according to any one of Embodiments 7-15, further comprising stirring the second lithium carbonate dispersion at 1000 rpm to 2500 rpm for 10 to 20 min before forming the second grinding suspension.
[0148] Embodiment 17. The method according to any one of embodiments 7-16, wherein after the second process, the BET surface area of the lithium carbonate particles increases by 5 to 67 times
[0149] Embodiment 18. The method according to any one of embodiments 7-17, wherein after the second process, the lithium carbonate particles have a thickness of about 10 m 2 / g to 25m 2 BET surface area between
[0150] Embodiment 19. A method for preparing lithium carbonate, comprising a first process followed by a second process,
[0151] The first process comprises:
[0152] The first lithium carbonate dispersion is formed by combining lithium carbonate particles in a first dispersion medium, wherein the lithium carbonate particles have a D between 5 μm and 8 μm. v (50);
[0153] forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO2) particles to a first lithium carbonate dispersion; and
[0154] grinding the first grinding suspension at a first predetermined speed for a first predetermined time period, the first predetermined speed being between 600 rpm and 1400 rpm, and the first predetermined time period being between 50 min and 250 min; and
[0155] The second process includes:
[0156] forming a second lithium carbonate dispersion by combining a plurality of lithium carbonate particles produced by the first process in a second dispersion medium;
[0157] forming a second grinding suspension by adding a second plurality of zirconium oxide (ZrO2) particles to a second lithium carbonate dispersion; and
[0158] grinding the second grinding suspension at a second predetermined speed for a second predetermined time period, the second predetermined speed being between 1200 rpm and 1800 rpm, and the second predetermined time period being between 150 min and 550 min, wherein after the second process,
[0159] After the second process, the lithium carbonate particles have a thickness of 15 m 2 / g to 25m 2 / g of BET surface area.
[0160] Embodiment 20. The method according to embodiment 19, wherein after the second process, the lithium carbonate particles have a thickness of 17.5 m 2 / g to 22.5m 2 / g of BET surface area.
[0161] Embodiment 21. A battery comprising:
[0162] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises:
[0163] Adhesives;
[0164] Conductive materials;
[0165] A negative electrode active material; and
[0166] A positive electrode comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises:
[0167] Adhesives;
[0168] Conductive materials;
[0169] positive electrode active material; and
[0170] A plurality of lithium carbonate (Li2CO3) particles, the particles having a 2 / g to 25m 2 / g;
[0171] Partitions; and
[0172] Non-aqueous electrolytes.
[0173] Embodiment 22. A battery according to Embodiment 21, wherein the negative electrode comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-carbon composite.
[0174] Embodiment 23. A battery according to Embodiment 21 or 22, wherein the positive electrode active material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0175] Embodiment 24. The battery of any one of Embodiments 21-23, wherein the lithium carbonate particles comprise at least 98 wt% lithium carbonate.
[0176] Embodiment 25. The battery of any one of Embodiments 21-24, wherein the lithium carbonate particles comprise at least 99 wt% lithium carbonate.
[0177] Embodiment 26. A battery according to any one of Embodiments 21-25, wherein the BET surface area of the lithium carbonate particles is between 15 m 2 / g to 25m 2 / g.
[0178] Embodiment 27. A battery according to any one of Embodiments 21-26, wherein the BET surface area of the lithium carbonate particles is 17.5 m 2 / g to 22.5m 2 / g.
[0179] Embodiment 28. A battery according to any one of Embodiments 21-27, wherein the lithium carbonate particles have a D between 0.08 μm and 0.43 μm. v (50).
[0180] Embodiment 29. A battery according to any one of Embodiments 21-28, wherein the lithium carbonate particles have a D between 0.015 μm and 0.5 μm. n (50).
[0181] Embodiment 30. The battery according to any one of Embodiments 21-29, wherein the positive electrode active material layer comprises 0.3 wt % to 1.0 wt % of lithium carbonate particles.
[0182] Embodiment 31. A lithium ion battery, comprising:
[0183] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises:
[0184] Adhesives;
[0185] Conductive materials; and
[0186] Negative electrode active material;
[0187] A positive electrode comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises:
[0188] Adhesives;
[0189] Conductive materials;
[0190] positive electrode active material; and
[0191] A plurality of lithium carbonate (Li2CO3) particles, the particles having:
[0192] In 10m 2 / g to 25m 2 / g;
[0193] D between 0.08 μm and 0.43 μm v (50); and
[0194] D between 0.015 μm and 0.5 μm n (50);
[0195] Partitions; and
[0196] Non-aqueous electrolytes.
[0197] Embodiment 32. A lithium ion battery according to Embodiment 31, wherein the negative electrode active material comprises a silicon-carbon composite.
[0198] Embodiment 33. A lithium ion battery according to Embodiment 31 or 32, wherein the negative electrode active material layer comprises 90 weight percent (wt%) to 99 wt% of the silicon carbon composite.
[0199] Embodiment 34. A lithium ion battery according to any one of Embodiments 31-33, wherein the positive electrode active material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0200] Embodiment 35. A lithium ion battery according to any one of Embodiments 31-34, wherein the positive electrode active material layer comprises 90 wt% to 99 wt% of LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0201] Embodiment 36. A lithium ion battery according to any one of Embodiments 31-35, wherein the positive electrode active material layer comprises 0.3 wt% to 1.0 wt% of lithium carbonate particles.
[0202] Embodiment 37. A lithium ion battery according to any one of Embodiments 31-36, wherein the BET surface area of the lithium carbonate particles is 15 m 2 / g to 25m 2 / g.
[0203] Embodiment 38. A lithium ion battery according to any one of Embodiments 31-37, wherein the BET surface area of the lithium carbonate particles is 17.5 m 2 / g to 22.5m 2 / g.
[0204] Embodiment 39. A lithium-ion battery according to any one of Embodiments 31-38, characterized in that the battery is a jelly-roll type battery.
[0205] Embodiment 40. A method of manufacturing a positive electrode for a lithium ion battery, the method comprising:
[0206] A positive electrode slurry is coated on a positive electrode current collector, wherein the positive electrode slurry comprises:
[0207] Adhesives;
[0208] Conductive materials;
[0209] positive electrode active material; and
[0210] A plurality of lithium carbonate (Li2CO3) particles, the particles having a 2 / g to 25
[0211] m 2 / g of BET surface area.
[0212] Embodiment 41. The method according to embodiment 40, wherein the BET surface area of the lithium carbonate particles is between 15 m 2 / g to 25m 2 / g.
[0213] Embodiment 42. A method according to Embodiment 40 or 41, wherein the BET surface area of the lithium carbonate particles is between 17.5 m 2 / g to 22.5m 2 / g.
[0214] Embodiment 43. The method according to any one of Embodiments 40-42, wherein the lithium carbonate particles have a D between 0.08 μm and 0.43 μm. v (50).
[0215] Embodiment 44. The method according to any one of Embodiments 40-43, wherein the lithium carbonate particles have a D between 0.015 μm and 0.5 μm. n (50).
[0216] Embodiment 45. A method according to any one of Embodiments 40-44, wherein the positive electrode slurry comprises 0.3 wt% to 1.0 wt% of lithium carbonate particles.
[0217] Embodiment 46. A method according to any one of Embodiments 40-45, wherein the positive electrode active material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0218] Embodiment 47. The method according to any one of embodiments 40-46, wherein the positive electrode slurry comprises 90 wt% to 99 wt% of LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0219] Embodiment 48. A method for manufacturing a battery, comprising the method for manufacturing a positive electrode according to any one of Embodiments 40-47, the method for manufacturing a battery further comprising a method for manufacturing a negative electrode, the method for manufacturing a negative electrode comprising coating a negative electrode slurry onto a negative electrode current collector,
[0220] The negative electrode slurry comprises:
[0221] Adhesives;
[0222] Conductive materials; and
[0223] Negative electrode active material.
[0224] Embodiment 49. A method according to Embodiment 48, wherein the negative electrode active material comprises a silicon-carbon composite.
[0225] Embodiment 50. The method according to Embodiment 48 or 49, wherein the negative electrode slurry comprises 90 wt% to 99 wt% of the silicon-carbon composite.
Claims
1. A plurality of lithium carbonate (Li2CO3) particles, comprising: at least 98 weight percent (wt%) lithium carbonate, the plurality of lithium carbonate (Li2CO3) particles having: D between 0.08 μm and 0.43 μm v (50); D between 0.015 μm and 0.5 μm n (50); and In 10m 2 / g to 25m 2 / g of BET surface area.
2. A plurality of lithium carbonate (Li2CO3) particles according to claim 1, wherein the D v (50) Between 0.15 μm and 0.35 μm.
3. The plurality of lithium carbonate (Li2CO3) particles according to claim 1, wherein the D n (50) Between 0.03 μm and 0.3 μm.
4. The plurality of lithium carbonate (Li2CO3) particles according to claim 1, wherein the BET surface area is between 15 m 2 / g to 25m 2 / g.
5. The plurality of lithium carbonate (Li2CO3) particles according to claim 4, wherein the BET surface area is between 17.5 m 2 / g to 22.5m 2 / g.
6. The plurality of lithium carbonate (Li2CO3) particles of claim 1, wherein the lithium carbonate particles comprise at least 99 wt% lithium carbonate.
7. The plurality of lithium carbonate (Li2CO3) particles of claim 1, wherein the lithium carbonate particles contain no more than 1.75 wt% impurities.
8. A method for preparing lithium carbonate, comprising: A first process and a second process, wherein the first process comprises: The first lithium carbonate dispersion is formed by combining lithium carbonate particles in a first dispersion medium, wherein the lithium carbonate particles have a D between 5 μm and 8 μm. v (50); forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO2) particles to a first lithium carbonate dispersion; and grinding the first grinding suspension at a first predetermined speed for a first predetermined time period, the first predetermined speed being between 500 rpm and 1500 rpm, and the first predetermined time period being between 30 min and 300 min; and The second process includes: forming a second lithium carbonate dispersion by combining a plurality of lithium carbonate particles produced by the first process in a second dispersion medium; forming a second grinding suspension by adding a second plurality of zirconium oxide (ZrO2) particles to a second lithium carbonate dispersion; and The second grinding suspension is ground at a second predetermined speed for a second predetermined period of time, the second predetermined speed being between 1000 rpm and 2000 rpm, and the second predetermined period of time being between 60 min and 600 min.
9. The method of claim 8, wherein the first predetermined speed is between 600 rpm and 1400 rpm, and the first predetermined time period is between 50 min and 250 min.
10. The method of claim 8, wherein the second predetermined speed is between 1200 rpm and 1800 rpm, and the second predetermined time period is between 150 min and 550 min.
11. The method according to claim 8, wherein the first dispersion medium comprises at least one of the following: methanol, ethanol, propanol, or N-methyl-2-pyrrolidone. 12 . The method according to claim 8 , wherein the second dispersion medium comprises at least one of the following: methanol, ethanol, propanol, or N-methyl-2-pyrrolidone.
13. The method of claim 8, wherein the first plurality of zirconium oxide particles have an average diameter between 1.00 mm and 1.80 mm.
14. The method of claim 8, wherein the second plurality of zirconium oxide particles have an average diameter between 0.20 mm and 1.20 mm.
15. The method of claim 8, wherein after the second process, the lithium carbonate (Li2CO3) particles have a D between 0.08 μm and 0.43 μm. v (50) and D between 0.015 μm and 0.5 μm n (50).
16. The method according to claim 8, further comprising stirring the first lithium carbonate dispersion at 30 rpm to 1000 rpm for 10 min to 20 min before forming the first grinding suspension.
17. The method according to claim 8, further comprising stirring the second lithium carbonate dispersion at 1000 rpm to 2500 rpm for 10 to 20 min before forming the second grinding suspension.
18. The method of claim 8, wherein after the second process, the BET surface area of the lithium carbonate particles increases by 5 to 67 times.
19. The method according to claim 8, wherein after the second process, the lithium carbonate particles have a thickness of 10 m 2 / g to 25m 2 / g of BET surface area.
20. A method for preparing lithium carbonate, comprising a first process and a second process, The first process includes: The first lithium carbonate dispersion is formed by combining lithium carbonate particles in a first dispersion medium, wherein the lithium carbonate particles have a D between 5 μm and 8 μm. v (50); forming a first grinding suspension by adding a first plurality of zirconium oxide (ZrO2) particles to a first lithium carbonate dispersion; and grinding the first grinding suspension at a first predetermined speed for a first predetermined time period, the first predetermined speed being between 600 rpm and 1400 rpm, and the first predetermined time period being between 50 min and 250 min; as well as The second process includes: forming a second lithium carbonate dispersion by combining a plurality of lithium carbonate particles produced by the first process in a second dispersion medium; forming a second grinding suspension by adding a second plurality of zirconium oxide (ZrO2) particles to a second lithium carbonate dispersion; and grinding the second grinding suspension at a second predetermined speed for a second predetermined time period, the second predetermined speed being between 1200 rpm and 1800 rpm, and the second predetermined time period being between 150 min and 550 min, wherein after the second process, After the second process, the lithium carbonate particles have a thickness of 15 m 2 / g to 25m 2 / g of BET surface area.
21. The method of claim 20, wherein after the second process, the lithium carbonate particles have a thickness of 17.5 m 2 / g to 22.5m 2 / g of BET surface area.
22. A battery comprising: The negative electrode comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises: Adhesives; Conductive materials; and Negative electrode active material; A positive electrode comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises: Adhesives; Conductive materials; positive electrode active material; and A plurality of lithium carbonate (Li2CO3) particles, wherein the plurality of lithium carbonate (Li2CO3) particles have a thickness of 10 m 2 / g to 25m 2 / g; Partitions; and Non-aqueous electrolytes.
23. The battery of claim 22, wherein the lithium carbonate particles comprise at least 98 wt% lithium carbonate.
24. The battery of claim 23, wherein the lithium carbonate particles comprise at least 99 wt% lithium carbonate.
25. The battery according to claim 22, wherein the BET surface area of the lithium carbonate particles is between 15 m 2 / g to 25m 2 / g.
26. The battery of claim 25, wherein the BET surface area of the lithium carbonate particles is between 17.5 m 2 / g to 22.5m 2 / g.
27. The battery of claim 22, wherein the lithium carbonate particles have a D between 0.08 μm and 0.43 μm. v (50).
28. The battery of claim 22, wherein the lithium carbonate particles have a D between 0.015 μm and 0.5 μm. n (50). 29 . The battery according to claim 22 , wherein the positive electrode active material layer comprises 0.3 wt % to 1.0 wt % of lithium carbonate particles.
30. The battery of claim 22, wherein the negative electrode comprises a negative electrode active material comprising a carbon silicon composite; and The positive electrode active material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2.
31. A lithium ion battery, comprising: The negative electrode comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises: Adhesives; Conductive materials; as well as Negative electrode active material; A positive electrode comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises: Adhesives; Conductive materials; positive electrode active material; and A plurality of lithium carbonate (Li2CO3) particles, wherein the plurality of lithium carbonate (Li2CO3) particles have: In 10m 2 / g to 25m 2 / g; D between 0.08 μm and 0.43 μm v (50); as well as D between 0.015 μm and 0.5 μm n (50); Partitions; as well as Non-aqueous electrolytes.
32. The lithium ion battery of claim 31, wherein the positive electrode active material layer comprises 0.3 wt% to 1.0 wt% of lithium carbonate particles.
33. The lithium ion battery of claim 31, wherein the BET surface area of the lithium carbonate particles is between 15 m 2 / g to 25m 2 / g.
34. The lithium ion battery of claim 33, wherein the lithium carbonate particles have a BET surface area of 17.5 m 2 / g to 22.5m 2 / g.
35. The lithium ion battery of claim 31 , wherein the battery is a jelly roll battery.
36. The lithium ion battery of claim 31, wherein the negative electrode active material comprises a silicon carbon composite.
37. The lithium ion battery of claim 36, wherein the negative active material layer comprises 90 weight percent (wt%) to 99 wt% of the silicon carbon composite.
38. The lithium ion battery of claim 31, wherein the positive electrode active material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2.
39. The lithium ion battery of claim 38, wherein the positive electrode active material layer comprises 90 wt% to 99 wt% of LiNi 0.8 Co 0.1 Mn 0.1 O2.
40. A method for manufacturing a positive electrode for a lithium ion battery, the method comprising: A positive electrode slurry is coated on a positive electrode current collector, wherein the positive electrode slurry comprises: Adhesives; Conductive materials; Positive electrode active material; as well as A plurality of lithium carbonate (Li2CO3) particles, wherein the plurality of lithium carbonate (Li2CO3) particles have a thickness of 10 m 2 / g to 25m 2 / g of BET surface area.
41. The method of claim 40, wherein the lithium carbonate particles have a BET surface area of 15 m 2 / g to 25m 2 / g.
42. The method of claim 41, wherein the lithium carbonate particles have a BET surface area of 17.5 m 2 / g to 22.5m 2 / g.
43. The method of claim 40, wherein the lithium carbonate particles have a D between 0.08 μm and 0.43 μm. v (50).
44. The method of claim 40, wherein the lithium carbonate particles have a D between 0.015 μm and 0.5 μm. n (50).
45. The method of claim 40, wherein the cathode slurry comprises 0.3 wt% to 1.0 wt% of lithium carbonate particles.
46. The method of claim 40, wherein the positive electrode active material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2.
47. The method according to claim 46, wherein the positive electrode slurry comprises 90 wt% to 99 wt% of LiNi 0.8 Co 0.1 Mn 0.1 O2.
48. A method for manufacturing a battery, comprising the method for manufacturing a positive electrode according to claim 40, the method for manufacturing a battery further comprising a method for manufacturing a negative electrode, the method for manufacturing a negative electrode comprising coating a negative electrode slurry onto a negative electrode current collector, The negative electrode slurry comprises: Adhesives; Conductive materials; and Negative electrode active material.
49. The method of claim 48, wherein the negative electrode active material comprises a silicon-carbon composite.
50. The method of claim 49, wherein the negative electrode slurry comprises 90 wt% to 99 wt% of the silicon-carbon composite.